Correction: Anticoagulant rodenticide exposure and toxicosis in bald eagles (Haliaeetus leucocephalus) and golden eagles (Aquila chrysaetos) in the United States. - Kevin D Niedringhaus; Nicole M Nemeth; Samantha Gibbs; Jared Zimmerman; Lisa Shender; Michelle van Deventer; Kate Slankard; Heather Fenton; Charlie Bahnson; Martha Frances Dalton; Elizabeth J Elsmo; Robert Poppenga; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0246134.].